A more cerebral cortex. - Anderson, M. (IEEE spectrum)
Intrinsity boosts the brainpower of a cellphone chip to the level of a PC. It had taken the 650-megahertz ARM Cortex-A8-a CPU designed for smartphones, licensed to Samsung by ARM Holdings-and hot-rodded it into a 1-gigahertz processor dubbed Hummingbird. The result could, with Samsung's backing, power an impressive portion of the next generation of must-have mobile devices. Some even speculate that Apple itself will put Hummingbird in a coming upgrade to its iPhone. It's all happening very quickly for a start-up that still shares office space with a local magazine and a dentist.